Small Spirits Native American Dolls from the National Musuem of the American Indian - Lenz, Mary Jane (2004)
Mary Jane Lenz's insightful, authoritative text discusses the intriguing roles dolls have played in Native American cultures and explores their significance today, while historical photographs bring to life the people who made and used these remarkable creations. Featuring a superb selection from the museum's collections, Lenz's landmark book will appeal to scholar, collector, and general reader alike.